Bigbook sebagai Sarana Literasi Inklusif bagi Anak Usia Dini di Sekolah Multikultural (Studi TK Satu Atap Wonco Kota Baubau): Bigbook as an Inclusive Literacy Tool for Early Childhood in Multicultural Schools (Study of Wonco One-Roof Kindergarten in Baubau City) - Risman, Kadar; Arifin, Syamsul; Ishomuddin, Ishomuddin; Meylandri, Yohana (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to analyze the effectiveness of Bigbook as an inclusive literacy tool for instilling multicultural values in early childhood education. The research was conducted at TK Satu Atap Wonco, Baubau City, located within a socially diverse community regarding religion and ethnicity. Participatory Action Research (PAR) was a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and documentation. The intervention was structured into three thematic sessions: religious literacy, ethnic diversity awareness, and prosocial behavior development. The findings reveal that Bigbook effectively facilitated children's understanding of interfaith symbols and practices, encouraged ethnic awareness through visual representation, and nurtured prosocial behaviors such as sharing, empathy, and cooperation. Beyond serving as a visual medium, Bigbook was a narrative tool that integrated children's cognitive and affective development. The responsiveness and contextual awareness of the teachers significantly supported the success of this inclusive literacy program. This study concludes that Bigbook holds substantial potential as a pedagogical strategy in multicultural education at the early childhood level, offering an adaptive, contextual, and reflective approach. It further contributes to the development of inclusive education policy within pluralistic societies.